Forestry, poverty, and rural development: perspectives from the bamboo subsector - Ruíz Pérez, M.; Belcher, B.; Maoyi Fu; Xiaosheng Yang (Resources for the Future and Center for International Forestry Research, 2003)
The chapter begins with a summary of the state of rural poverty in China and the potential role of forestry. It continues with a general discussion of the bamboo sector and the evidence from the research regarding the household income effects of the rapid expansion on bamboo production. Bamboo in all of its many uses is the third most important forest products in China. It is a particularly useful product for inquiry because it has not been subject to as many policy restrictions as commercial timber. Therefore, its recent history is more representative of the impacts that unfettered forestry-sector development could have on households incomes and regional development. It than observes that many households have benefited from the expansion in bamboo production, but the poorest have not been the greatest benefactors. Furthermore, bamboo seems to have a role in development, but its importance declines as development progresses. These observations on bamboo do not reject the standard arguments about forestry as a development leader, However, they do prompt the authors to urge caution in their applications, particularly with regard to assistance for the very poorest.